Analisis Strategi Pemasaran Berbasis Syariah pada Kiswah Moeslem Fashion - Mashadi, Ali Imron (FADZAT: Jurnal Ekonomi Syariah, 2023)
This study examines the implementation of Sharia-based marketing strategies at Kiswah Moeslem Fashion, a business located on Jl. Hayam Wuruk No 22 Pacet, focusing on the production of Muslim attire including Mukena, Jilbab, Baju Koko, and Gamis. In the burgeoning Muslim fashion industry, particularly in Indonesia, incorporating Sharia principles into marketing strategies not only demonstrates a commitment to ethical and spiritual values but also opens vast market opportunities. The integration of Sharia principles in marketing has been shown to enhance customer trust and loyalty, providing a competitive edge in a saturated market. This research explores how such strategies not only meet the functional needs of consumers but also resonate with their spiritual aspirations, thereby differentiating Kiswah Moeslem Fashion in a competitive landscape. Additionally, the study highlights the significance of sustainability and ethical business practices in influencing consumer purchasing decisions, aligned with Sharia principles, adding further value to the brand. Challenges in implementing Sharia-based marketing strategies are also discussed, alongside recommendations for leveraging technology, focusing on sustainability and ethics, strategic collaborations, consumer education, and continuous monitoring and evaluation. The findings suggest that adopting Sharia-based marketing strategies is a viable approach for achieving success in the Muslim fashion market, fostering significant differentiation and strengthening customer relationships for sustainable growth.